Psychological predictors of competitive levels in badminton athletes: a gender-stratified analysis - Wang, Y.; Li, Z.; Xie, X.; Yang, G.; Chen, T.; Wang, H. (Frontiers in Psychology, 2025)
Introduction: Character traits are thought to influence competitive success in racket sports, yet their predictive value for competitive level in badminton and potential gender-specific pathways remain unclear. This study aimed to investigate the predictive role of character traits on competitive level in badminton athletes, with a particular focus on gender-specific pathways.